PELATIHAN PEMBUATAN PUPUK ORGANIK BERBAHAN BAKU SUMBEDAYA LOKAL GUNA MENDUKUNG KETAHANAN PANGAN LOKAL DI KABUPATEN LOMBOK TIMUR - Rizal Ahmadi; Muhammad Joni Iskandar; Hernawati Hernawati (Universitas Mataram, 2025)
The agricultural sector faces significant challenges related to production sustainability and environmental preservation due to the excessive use of chemical fertilizers, which degrades soil quality and increases production costs. The utilization of organic fertilizers derived from local resources offers a strategic solution to support sustainable agriculture. This program aimed to provide training and assistance to the Tundak Karya 2 Farmer Group in producing organic fertilizer using locally available materials such as livestock manure, rice straw, rice bran, molasses, and dolomite. The training was conducted on 6 August 2025 in Batu Putik Village, Keruak District, East Lombok Regency, using a Participatory Action Program (PAP) approach through stages of socialization, demonstration, hands-on practice (learning by doing), and evaluation using pre-tests and post-tests. The results showed a significant improvement in the group members’ technical skills, with more than 85% mastery of material mixing procedures, fermentation processes, storage techniques, and final fertilizer production. Participants also demonstrated high enthusiasm and increased awareness of reducing dependence on chemical fertilizers by independently utilizing agricultural and livestock waste. Overall, this program effectively strengthened farmer group self-reliance and holds potential as a model for sustainable agriculture based on local resource utilization.